Rocket measurements of electron influx across the midday auroral oval - McEwen, D. J.; Steele, D. P. (Canadian Journal of Physics, 1986)
A Black Brant IV rocket was flown through the dayside cusp from Cape Parry, N.W.T., (λ = 75°) on December 6, 1981. It flew to an apogee of 603 km and emerged into the polar cap at λ = 77°. The flight was through a fairly stable midday cusp at approximately 1230 magnetic local time. A very soft electron spectrum was observed, which was comparable with a Maxwellian distribution of E 0 ≤ 10 eV. At energies above 100 eV, it was better fitted by a power law of form E −2 . The energy flux was 0.2 erg∙cm −2 ∙s −1 ∙sr −1 (1 erg = 0.1 μJ), with most of this energy being deposited at heights below 400 km. The λ6300 emission intensity measured from the ground was about 1 kR, somewhat below average midday-cusp λ6300 intensity values. Three short intervals of electron energization were observed during the 11 min the rocket was within the cusp.